Effects of autonomic disruption and inactivity on venous vascular function - Wecht, Jill M; de Meersman, Ronald E; Weir, Joseph P; Bauman, William A; Grimm, David R (American journal of physiology. Heart and circulatory physiology, 2000)
1  Veterans Affairs Medical Center, Spinal Cord Damage Research Center and Medical Services, Bronx 10468; 2  Departments of Medicine and 3  Rehabilitation Medicine, Mount Sinai School of Medicine, New York 10029; 4  Department of Rehabilitation Medicine, College of Physicians and Surgeons, Columbia University, New York 10032; and 5  University of Osteopathic Medicine and Health Sciences, Des Moines, Iowa 50312 The effects of autonomic disruption and inactivity were studied on the venous vascular system. Forty-eight subjects, 24 with spinal cord injury (SCI) and 12 sedentary and 12 active able-bodied controls, participated in this study. Peripheral autonomic data were obtained to estimate sympathetic vasomotor control [low-frequency component of systolic blood pressure (LF SBP )]. Vascular parameters were determined using strain-gauge venous occlusion plethysmography: venous capacitance (VC), venous emptying rate (VER), and total venous outflow (VO t ). An additional vascular parameter was calculated: venous compliance [(VC/occlusion pressure) × 100]. VC and VO t were significantly different (SCI < sedentary < active). VER adjusted for VC was not different for any group comparison, whereas venous compliance was significantly lower in the SCI group than in the able-bodied groups and in the sedentary group compared with the active group. Regression analysis for the total group revealed a significant relationship between LF SBP and venous compliance ( r  = 0.64,  P < 0.0001). After controlling for LF SBP through analysis of covariance, we found that mean differences for all venous vascular parameters did not change from unadjusted mean values. Our findings suggest that in subjects with SCI, the loss of sympathetic vasomotor tone contributes more than inactivity to reductions in venous vascular function. Heightened VC, VO t , vasomotor tone, and venous compliance in the active group compared with the sedentary group imply that regular endurance training contributes to optimal venous vascular function and peripheral autonomic integrity. spinal cord injury; vasomotor tone; venous occlusion plethysmography; autonomic nervous system